Experiments with a Sorghastrum pellitum (Hack.) Parodi population to reintroduce it in the sandy areas (Semiárida, 2020)
In natural areas, the changes produced by fence and selective grazing of cattle led to the loss of some species and increasing others. Sorghastrum pellitum (red grass), fodder pasture important, has been virtually eliminated or reduced to marginal areas due to livestock use. The aim of this study was to evaluate the behavior of this species from seed germination and during a year of plant development. In spring 400 plants were established in field and their development was evaluated in this growing season. The results indicate a high sensitivity of seedlings to low temperatures. Once seedling stage past, the plants showed a good development with growth even in periods of low rainfall.
Keywords: Sorghastrum pellitum; Germination; Resistance lo frost; Implantation